Pengaruh Knowledge Sharing dan Total Qualit Management terhadap Perilaku Produktif Karyawan pada PT. Nipsea Paint and Chemicals Departemen Pylox Plant Purwakarta: Penelitian - Ela Laela; Shifa Fauziah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research was conducted aiming to determine the influence of knowledge sharing and total quality management on employee productive behavior at PT. Nipsea Paint and Chemicals Department Pylox Plant Purwakarta. This type of research is quantitative research. The sample in this research is 72 respondents. The sampling technique used in this study was the probability sampling technique, while the method used was simple random sampling. Data analysis used in this study was multiple linear regression analysis, t-test, f-test, and coefficient of determination (R2) using IBM SPSS 26. The results of the study showed that: 1) Knowledge Sharing has a positive and significant effect on employee productive behavior at PT. Nipsea Paint and Chemicals Department Pylox Plant Purwakarta; 2) Total Quality Management has a positive and significant effect on employee productive behavior at PT. Nipsea Paint and Chemicals Department Pylox Plant Purwakarta; 3) Knowledge Sharing and Total Quality Management simultaneously affect employee productive behavior at PT. Nipsea Paint and Chemicals Department Pylox Plant Purwakarta. Knowledge Sharing and Total Quality Management have an influence of 78.3% on employee productive behavior, while the remaining 21.7% is influenced by factors not examined in this study.